Naso-ethmoid schwannoma with intracranial extension: case report Schwannoma naso-etmoidal com extensão intracraniana: relato de caso - Mario G. Siqueira; Erik Jennings; Osmar J.S. Moraes; Marco Tulio S. Santos; Nelci Zanon; Belmiro J. Mattos; Luiz Belmonte Netto (Arquivos de Neuro-Psiquiatria, 2001)
Intranasal schwannomas are rare lesions, specially when they present with an intracranial extension. The fifth case in the medical literature of a naso-ethmoid schwannoma with extension into the anterior cranial fossa is presented. The magnetic resonance findings and the details of the combined intracranial / transfacial operative approach used are described. The possible origin and the clinical characteristics of this rare lesion are reviewed. Schwannomas intranasais são lesões raras, principalmente quando apresentam um extensão intracraniana. Estamos apresentando o quinto caso da literatura médica de um schwannoma naso-etmoidal com extensão para o interior da fossa craniana anterior. São descritos os achados da ressonância magnética e os detalhes da via de acesso cirúrgico combinada intracraniana/transfacial. A possível origem e as características clínicas dessa lesaõ rara são revistas.